PENGARUH TEKNOLOGI DAN LINGKUNGAN TERHADAP PENGGUNAAN MEDIA SOSIAL CLOUD KITCHEN DI INDONESIA PADA MASA PANDEMI COVID-19 - Amelda Pramezwary; Juliana Juliana; Keke Melinda; Kharis Dwi Nugraha; Tasha Gracia Haslin (JNSTA ADPERTISI JOURNAL, 2021)
Technology develops over time and the level of sophistication is even higher. Thanksi toi newi technologiesi suchi asi thei interneti alli humani needsi cani bei met, ranging ifrom sociali needs, accessing information, to satisfaction on ithe ifulfillment iof ientertainment needs. Nowadays, iits ipresence iis more widely iused ias isocial imedia iby the public. Environments can shape the character of an individual having a high intensity iin ithe iuse iof isocial media. Due to the COVID-19 outbreak, many people are reluctant to leave.. Home. Cloud kitchen-based kitchen company became ione ofi thei sectorsi thati successfully developed when the coronavirus outbreak hit Indonesia. Cloud kitchen is a catering service concept that provides delivery services performed directly by restaurants. iThe purposei iof ithis istudy is ito ianalyze ithe influencei ofi technology iand the ienvironment ion ithe use ofi isocial mediai cloud kitchen iin Indonesia duringi ithe covid-19i ipandemic. iIn ithis iistudy, sampling based on purposive sampling technique. The resultsi of data analysis obtained a positive and significant influence between technology and the environment on the use of isocial imedia cloud kitchen iin Indonesia duringi ithe Covid-19i iPandemic. The more dominant variable of its influence on social media use cloud kitchen is environmental variables.